Tacrolimus-binding protein FKBP8 directs myosin light chain kinase-dependent barrier regulation and is a potential therapeutic target in Crohn’s disease - Zuo, Li; Kuo, Wei-Ting; Cao, Feng; Chanez-Paredes, Sandra D; Zeve, Daniel; Mannam, Prabhath; Jean-François, Léa; Day, Anne; Vallen Graham, W; Sweat, Yan Y; Shashikanth, Nitesh; Breault, David T; et al. (Gut, 2023)
ObjectiveIntestinal barrier loss is a Crohn’s disease (CD) risk factor. This may be related to increased expression and enzymatic activation of myosin light chain kinase 1 (MLCK1), which increases intestinal paracellular permeability and correlates with CD severity. Moreover, preclinical studies have shown that MLCK1 recruitment to cell junctions is required for tumour necrosis factor (TNF)-induced barrier loss as well as experimental inflammatory bowel disease progression. We sought to define mechanisms of MLCK1 recruitment and to target this process pharmacologically.DesignProtein interactions between FK506 binding protein 8 (FKBP8) and MLCK1 were assessed in vitro. Transgenic and knockout intestinal epithelial cell lines, human intestinal organoids, and mice were used as preclinical models. Discoveries were validated in biopsies from patients with CD and control subjects.ResultsMLCK1 interacted specifically with the tacrolimus-binding FKBP8 PPI domain. Knockout or dominant negative FKBP8 expression prevented TNF-induced MLCK1 recruitment and barrier loss in vitro. MLCK1-FKBP8 binding was blocked by tacrolimus, which reversed TNF-induced MLCK1-FKBP8 interactions, MLCK1 recruitment and barrier loss in vitro and in vivo. Biopsies of patient with CD demonstrated increased numbers of MLCK1-FKBP8 interactions at intercellular junctions relative to control subjects.ConclusionBinding to FKBP8, which can be blocked by tacrolimus, is required for MLCK1 recruitment to intercellular junctions and downstream events leading to immune-mediated barrier loss. The observed increases in MLCK1 activity, MLCK1 localisation at cell junctions and perijunctional MLCK1-FKBP8 interactions in CD suggest that targeting this process may be therapeutic in human disease. These new insights into mechanisms of disease-associated barrier loss provide a critical foundation for therapeutic exploitation of FKBP8-MLCK1 interactions.